Truth and veridicality in grammar and thought mood, modality, and propositional attitudes - Giannakidou, Anastasia 20./21. Jh; Mari, Alda 1973- (University of Chicago Press, 2021)
Can language directly access what is true, or is the truth judgment affected by the subjective, perhaps even solipsistic, constructs of reality built by the speakers of that language? The construction of such subjective representations is known as veridicality, and in this book Anastasia Giannakidou and Alda Mari deftly address the interaction between truth and veridicality in the grammatical phenomena of mood choice: the indicative and subjunctive choice in the complements of modal expressions and propositional attitude verbs. Combining several strands of analysis-formal linguistic semantics, syntactic theory, modal logic, and philosophy of language-Giannakidou and Mari's theory not only enriches the analysis of linguistic modality, but also offers a unified perspective of modals and propositional attitudes. Their synthesis covers mood, modality, and attitude verbs in Greek and Romance languages, while also offering broader applications for languages lacking systematic mood distinction, such as English. Truth and Veridicality in Grammar and Thought promises to shape longstanding conversations in formal semantics, pragmatics, and philosophy of language, among other areas of linguistics
Keywords: LANGUAGE ARTS & DISCIPLINES / General / bisacsh; Language and languages -- Philosophy; Sociolinguistics; Truth; Proposition; Soziolinguistik; Grammatik; Wahrheit; Sprachphilosophie